DISCRIMINATION OF Burkholderia mallei/pseudomallei FROM Burkholderia thailandensis BY SEQUENCE COMPARISON OF A FRAGMENT OF THE RIBOSOMAL PROTEIN S21 (RPSU) GENE. - Frickmann, H; Chantratita, N; Gauthier, Y; Gauthier, Y; Neubauer, H; Neubauer, H; Hagen, R; Hagen, R (2012)
Discrimination of Burkholderia (B.) pseudomallei and B. mallei from environmental B. thailandensis is challenging. We describe a discrimination method based on sequence comparison of the ribosomal protein S21 (rpsU) gene.The rpsU gene was sequenced in ten B. pseudomallei, six B. mallei, one B. thailandensis reference strains, six isolates of B. pseudomallei, and 37 of B. thailandensis. Further rpsU sequences of six B. pseudomallei, three B. mallei, and one B. thailandensis were identified via NCBI GenBank. Three to four variable base-positions were identified within a 120-base-pair fragment, allowing discrimination of the B. pseudomallei/mallei-cluster from B. thailandensis, whose sequences clustered identically. All B. mallei and three B. pseudomallei sequences were identical, while 17/22 B. pseudomallei strains differed in one nucleotide (78A>C). Sequences of the rpsU fragment of 'out-stander' reference strains of B. cepacia, B. gladioli, B. plantarii, and B. vietnamensis clustered differently.Sequence comparison of the described rpsU gene fragment can be used as a supplementary diagnostic procedure for the discrimination of B. mallei/pseudomallei from B. thailandensis as well as from other species of the genus Burkholderia, keeping in mind that it does not allow for a differentiation between B. mallei and B. pseudomallei.